Patient and clinician views on an app for rheumatoid arthritis disease monitoring: Function, implementation and implications. (18th May 2020) - Grainger, Rebecca; Townsley, Hermaleigh Roberta; Ferguson, Catherine Anna; Riley, Faye Ellen; Langlotz, Tobias; Taylor, William John
Abstract: Aim: Best practice management for rheumatoid arthritis (RA) involves regular clinical assessment of RA disease activity. This is not achievable with current rheumatology systems of care. We aimed to use opinions from people with RA and their specialist rheumatology healthcare professionals to inform development of a mobile app for people with RA for recording their disease activity data for potential integration into clinical service, and assess usability of the app. Method: In phase 1 we interviewed nine people with RA and seven healthcare professionals. In phase 2 we developed an app with professional software developers. In phase 3 we evaluated app usability for people with RA using the System Usability Scale (SUS). Results: Interview data showed four themes regarding functionality and implementation of a patient‐held app in RA care: (a) variable app acceptance and readiness; (b) app use to reduce barriers; (c) pros and cons of patient‐reported outcomes; and (d) allocation of clinics by need. The app developed has high usability in people with RA using the app on their own device for a month (SUS 79.5, n = 16) or using the app on a study device for 10 minutes (SUS 83, n = 100). Conclusion: People with RA and healthcare professionals have clearly identified features, benefits and risks of an app for self‐assessment of RA and incorporation into clinical care. An app developed informed by these opinions has high usability. Next steps are development and validation of a method of patient‐performed joint counts, and implementation, with evaluation, in the clinical setting.